Elemen Beat Dalam Babak Dua : Analisis Filem Polis Evo (2015) - Rosli Sareya; Zairul Anuar Md. Dawam; D. Maryama Ag. Daud (2018)
This study reveals the importance of beat elements in the second half of the confrontation in the action movie, "Polis Evo" (2015). The use of beat elements is aimed at increasing the intensity of the scenes which can increase the adrenaline of the audience when watching an action movie. A high and more intense beat in action scenes, for example, will lead to higher levels of emotional excitement and anxiety of the audience. Beat analysis affects the stage intensity of an action movie as demonstrated by Blake Snyder’s (2005) approach which he introduced the beat sheet element. The beat element consists of opening image, theme, set up, catalyst, debate, division, story, fun and games, mid-point, antagonist attack, “all is lost”, “dark night of the soul,” “three parts,” finale and final image. Blake Snyder’s beat element is aimed at making the storytelling more exciting for audiences. Additionally, this article will discuss the style element or movie language used by the director to visualize the scene. Audio styles, shotgun, editing techniques and mise-en-scene aspects will also increase the storytelling intensity of a movie making it more action packed through the narrative structure creating a great action movie to attract the attention of an audience.